2022
DOI: 10.3389/fcimb.2021.790418
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of Centrin in Leishmania braziliensis Using CRISPR-Cas9-Based Editing

Abstract: Leishmania braziliensis is the main causative agent of Tegumentary Leishmaniasis in the Americas. However, difficulties related to genome manipulation, experimental infection, and parasite growth have so far limited studies with this species. CRISPR-Cas9-based technology has made genome editing more accessible, and here we have successfully employed the LeishGEdit approach to attenuate L. braziliensis. We generated a transgenic cell line expressing Cas9 and T7 RNA polymerase, which was employed for the targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…Since the LdCen −/− parasite have growth defects in amastigote forms, but not in promastigotes 23 , 24 , this deletion prevents cell division and long-term persistence in animals (mice and hamsters) or in human macrophages ex vivo 23 . The same non-virulent characteristics of Centrin gene deletion were also observed in other species, like L. major , L. mexicana and L. braziliensis 25 27 . In pre-clinical studies, vaccination with LdCen −/− proved to be safe, protective and in mice (BALB/c and SCID), hamsters and dogs, after challenge with virulent parasites, in addition to cross-protection in animals challenged with L. braziliensis, L. infantum and L. mexicana 14 21 , 28 .…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Since the LdCen −/− parasite have growth defects in amastigote forms, but not in promastigotes 23 , 24 , this deletion prevents cell division and long-term persistence in animals (mice and hamsters) or in human macrophages ex vivo 23 . The same non-virulent characteristics of Centrin gene deletion were also observed in other species, like L. major , L. mexicana and L. braziliensis 25 27 . In pre-clinical studies, vaccination with LdCen −/− proved to be safe, protective and in mice (BALB/c and SCID), hamsters and dogs, after challenge with virulent parasites, in addition to cross-protection in animals challenged with L. braziliensis, L. infantum and L. mexicana 14 21 , 28 .…”
Section: Introductionsupporting
confidence: 75%
“…The data demonstrated that live attenuated parasite induced strong and durable protection against virulent secondary challenges 103 , indicating that is a good way to achieve protective immunity against Leishmania infection by vaccination. In our previous work, vaccination with the attenuated parasite proved to be safe, protective and persistent in mice (BALB/c and SCID), hamsters and dogs, after challenge with wild forms, in addition to cross-protection in animals challenged with L. braziliensis , L. infantum 14 18 , 27 , 40 . In addition, LdCen −/− MIF −/− immunized mice appear to clear infection in spleen and liver sooner than those immunized with LdCen −/− parasites.…”
Section: Discussionmentioning
confidence: 97%
“…Following this discovery, more recent studies on attenuation have utilized CRISPR to generate null mutants with high efficiency. Among the deleted targets are Centrin1 [29,34,36,71], eukaryotic translation initiation factor 4E-1 (EIF4E1) [72] and the noncatalytic component of the GPImannosyltransferase (GPI-MTI) complex [73].…”
Section: Genetic Manipulation For Selecting Live-attenuated Leishmaniamentioning
confidence: 99%
“…Several gene targets that encode proteins important for the selection of attenuated parasites have been reported, including arabino1,4-lactone oxidase (ALO) protein [32,83], cytochrome c oxidase complex component p27 [84][85][86], HSP70 type II heat shock protein [31,56,[102][103][104], centrin1 [29,[33][34][35][36]53,54,71,[117][118][119] and kharon1 [57][58][59]. Other target candidates have also shown potential, such as biopterin transporter (BT1) [37], dihydrofolate reductase/thymidylate synthase (DHFR-TS) [88] and Golgi GDP-mannose transporter (LPG2) [92,137].…”
Section: Genetically Engineered Live-attenuated Vaccine Candidatesmentioning
confidence: 99%
“…Promastigote parasites were maintained in Schneider medium (Sigma Chemical Co.) supplemented with 100 U/mL of penicillin, 100 μg/mL of streptomycin, and 10% heat-inactivated fetal calf serum (Life Technologies). Promastigotes were grown in airtight flasks (T25 [nonvented]), incubated upright in a 25°C incubator, and passaged every 3 days ( 4 ). Genomic DNA was extracted using the Wizard genomic DNA purification kit (Promega) following the manufacturer’s instructions.…”
Section: Announcementmentioning
confidence: 99%